Serial Changes in Exercise Capacity, NT-proBNP, and Adiponectin in Patients with Acute Coronary Syndrome before and after Phase II Rehabilitation as well as at the 12-Month Follow-Up - Hong Jin; Yuefei Liu; Bernd Schweikert; Harry Hahman; Lei Wang; Armin Imhof; Rainer Muche; Wolfgang König; Jürgen M. Steinacker (Cardiology Research and Practice)
Background. Acute coronary syndrome (ACS) causes pathophysiological changes in exercise capacity, N-terminal part of pro-brain natriuretic peptide (NT-proBNP), and adiponectin that impact the course of coronary artery disease and clinical outcomes after cardiac rehabilitation (CR). However, the serial changes and the relationship between the changes in these parameters for a prolonged term remain uninvestigated. Methods. Eighty-one patients with ACS underwent a three- or four-week CR program after acute care and were followed up for 12 months. Exercise capacity on a cycle ergometer and blood levels of NT-proBNP and adiponectin were determined before and after CR as well as at the 12-month follow-up. Results. Exercise capacity increased from 100 watts (in median) before CR to 138 watts after CR and 150 watts at 12 months. The NT-proBNP level (526 pg/ml before CR) remained almost unchanged after CR (557 pg/ml) and then decreased at 12 months (173 pg/ml). The adiponectin level (14.5 µg/ml before CR) increased after CR (16.0 µg/ml) and at 12 months (17.2 µg/ml). There was no significant correlation among the changes in these parameters at each observation time point. Conclusion. During the observation period from before CR to the 12-month follow-up, exercise capacity, NT-proBNP, and adiponectin underwent significant changes; however, these changes were independent from each other and not correlated linearly, and they provide complementary information in clinical practice. Thus, all these parameters should be included and determined at different time points for a prolonged period of time.